2006
DOI: 10.1038/nm1505
|View full text |Cite
|
Sign up to set email alerts
|

A selective Sema3A inhibitor enhances regenerative responses and functional recovery of the injured spinal cord

Abstract: Axons in the adult mammalian central nervous system (CNS) exhibit little regeneration after injury. It has been suggested that several axonal growth inhibitors prevent CNS axonal regeneration. Recent research has demonstrated that semaphorin3A (Sema3A) is one of the major inhibitors of axonal regeneration. We identified a strong and selective inhibitor of Sema3A, SM-216289, from the fermentation broth of a fungal strain. To examine the effect of SM-216289 in vivo, we transected the spinal cord of adult rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
295
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(316 citation statements)
references
References 49 publications
17
295
1
3
Order By: Relevance
“…The possible mechanism implicated is the arrangement of intraspinal neural circuits by the local axons regenerated most probably from interneurons, which make signal relay and synaptic connections with regenerated descending axonal tracts as previously described. 36,37 Our findings confirmed preservation of lumbar motoneurons and their functional axons in Gal-1-treated mice. Finally, a compensatory response below the lesion site by these lumbar motoneurons was ruled out by retransection experiments, which demonstrated that the locomotor recovery was dependent on site-specific regeneration.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The possible mechanism implicated is the arrangement of intraspinal neural circuits by the local axons regenerated most probably from interneurons, which make signal relay and synaptic connections with regenerated descending axonal tracts as previously described. 36,37 Our findings confirmed preservation of lumbar motoneurons and their functional axons in Gal-1-treated mice. Finally, a compensatory response below the lesion site by these lumbar motoneurons was ruled out by retransection experiments, which demonstrated that the locomotor recovery was dependent on site-specific regeneration.…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, previous studies showed expression of Sema3A within the transected spinal cord that was upregulated at the lesion site, peaking within 1 and 2 weeks after the injury. 36 Because of these particular kinetics, we propose that Gal-1 treatment should take place within a temporal window where its interactions with the NRP-1/PlexinA4 complex could lead to inhibition of Sema3A binding, allowing axonal regeneration of these tracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research focuses largely on improving neurological manifestations through the improvement of sensory function and locomotor function [1][2][3][4], but study of the bloodLi-Bing Ye and Xi-Chong Yu contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the role of guidance molecules is not limited to those that are expressed by oligodendrocytes. A recent study indicates that administration of a small molecule inhibitor of Sema3A, a guidance molecule that is expressed by the fibroblast component of the scar tissue (De Winter et al, 2002), leads to multiple beneficial effects including enhanced regenerative response from axons (Kaneko et al, 2006). Thus, the potential role of axon guidance molecules in restricting axon regeneration after CNS injury is not limited to white matter or myelin (see the review by Smith and colleagues in the current issue).…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%